(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
In this study, the lumpy skin disease virus was isolated on the lamb testis cell culture for the first time inIraq. Forty skin nodules were collected from cows suspected with lumpy skin disease (LSD) in Baghdadgovernorate. Real-time PCR detected LSD virus in 100% of these skin nodules. After that, the lamb testiscell culture was prepared for virus isolation. The prepared samples (0.5 ml) were inoculated into preparedlamb testis cell culture. Cytopathic effects (CPE) of the virus have appeared after 24hr post-inoculation andcompleted within 72hr. The noticed CPE were cell rounding, aggregation of cells, syncytia formation, anddetached of the cells from the cell sheet. Fluids of lamb testis cell culture were examined by the real-timePCR to confirm that the observed CPE was due to the LSD virus. Cell culture fluids were positive by thereal-time PCR (100%). Real-time PCR was sensitive for the detection of the LSD virus DNA in skin nodules,and it was a suitable confirmatory diagnosis tool of the virus in the tissue culture fluid. Finally, the locallyisolated LSD virus in this study is valuable in future studies for making a vaccine to control the disease.